Reciclaje y conciencia ambiental en estudiantes de quinto y sexto grado de nivel primaria en la Institución Educativa de la I.E. N° 60743 Enry Herve Linares Soto, Belén 2023 - Ramirez Yahuarcani, Griseña (2024)
The main objective of the research was to establish the relationship that exists between recycling and environmental awareness in fifth and sixth grade students at the Primary level at Educational Institution No. 60743 Enry Herve Linares Soto, Belén – 2023. A sample was considered. of 128 primary level students belonging to the educational institution. The instrument used was a questionnaire previously validated by expert judgment, and the data collection technique was the survey. As a result, we have a Pearson correlation coefficient rxy= 0.850, which indicates that there is a relationship between these variables, that is, that recycling and environmental awareness are significantly related.